Influence of Trust, Time Pressure and Complexity Factors in Judgment and Decision-Making in Auditing - Cleston Santos; Paulo Cunha (BBR: Brazilian Business Review)
This study aims to evaluate the interrelation of the influence of the factors trust (personal), time pressure (environmental) and complexity (task) in judgment and decision-making in theauditing field. As a research method, we undertook an experiment, with a 2x2x2 factorial composition. The final sample was composed of 126 independent auditors, distributed in eight random groups. The results indicated that a higher level of confidence increases the auditor’s propensity to perform the accounting adjustment and that time pressure and complexity decrease the auditor’s propensity to perform the proposed adjustment. These findings allow us to infer that the factors of trust, time pressure, and complexity, both individually and jointly influence judgment and decision-making. This study contributes to Behavioral Decision Theory, as in that the discussions are directed to assist auditing firms in their understanding of the joint and interactive effect of personal, environmental, and task factors in professional activities, and enable better planning and establishing criteria for audit working conditions.